2016
DOI: 10.31186/aa.19.2.167-172
|View full text |Cite
|
Sign up to set email alerts
|

Pertumbuhan Vegetatif Talas Satoimo dan Kultivar Lokal pada Dosis Pupuk Nitrogen yang Berbeda

Abstract: Taro (Colocasia esculenta L. Schott) is a plant that has an excellent economic and healthy value, as well as a great potential development of Bengkulu coastal area. That is because taro has wide adaptability, and can be consumed both as a staple food and healthy food alternative. This research was conducted to study the vegetative growth of two cultivars of taro given four different doses of nitrogen. This study applied a Randomized Complete Block Design (RCBD) with two factors. The first factor was the cultiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
1
0
2
Order By: Relevance
“…Plant height of California genotype (170,96 cm) was higher compared to Ketan, Talas Kuning, Jepang Hijau, and Satoimo (Table 1), while Satoimo (138,56 cm) and Jepanghijau (139,44 cm) has the lowest plant height compared to other genotypes. It is known that there are differences in the height of taro plants due to genetic influences [11]. Previous research found highly significant variation among taro varieties in terms of plant height [12][13].…”
Section: Resultsmentioning
confidence: 99%
“…Plant height of California genotype (170,96 cm) was higher compared to Ketan, Talas Kuning, Jepang Hijau, and Satoimo (Table 1), while Satoimo (138,56 cm) and Jepanghijau (139,44 cm) has the lowest plant height compared to other genotypes. It is known that there are differences in the height of taro plants due to genetic influences [11]. Previous research found highly significant variation among taro varieties in terms of plant height [12][13].…”
Section: Resultsmentioning
confidence: 99%
“…Tanaman Talas Sutra dan Talas Bentul memiliki tinggi 16% lebih besar dibandingkan dengan talas S26, namun tidak berbeda nyata dengan talas S24, S34, dan S36. Adanya perbedaan tinggi tanaman talas karena pengaruh genetipe telah diketahui (Yulian et al, 2016). IPGRI (1999) mengelompokkan tanaman talas berdasarkan tinggi tanaman ke dalam dwarf (<50 cm), medium (50-100 cm), tinggi (100-150), dan sangat tinggi (>150 cm).…”
Section: Morfologi Tanamanunclassified
“…Genotipe talas selain S20, S34, dan S36 tidak menunjukan penurunan bobot tajuk yang nyata pada pemberian air setiap 3 hari relatif terhadap pemberian setiap hari; artinya genotipegenotipe tersebut lebih toleran dibandingkan dengan S20, S34, dan S36. Hasil ini sejalan dengan penelitian Yulian et al (2016) bahwa genotipe memiliki peran penting dalam merespon perlakuan khususnya pada peubah bobot kering tajuk. Menurut Ganança et al (2018) secara umum cekaman kekeringan menurunkan bobot basah tajuk sekitar 29.74% pada semua kultivar talas; dan kultivar yang peka dapat menurun hingga 95% dibandingkan dengan kondisi kontrol.…”
Section: Bobot Tajukunclassified